Comparison of computed tomography‐guided percutaneous needle biopsy and endobronchial biopsy in the diagnosis of multifocal pulmonary lesions. Issue 6 (10th May 2019) - Li, Xiao‐Feng; Zheng, Li‐Li; He, Yu; Wang, Mao‐Shui
Abstract: Background: The retrospective study aimed to compare computed tomography (CT)‐guided percutaneous needle biopsy (PNB) and endobronchial biopsy (EB) in the diagnosis of multifocal pulmonary lesions with endobronchial involvement. Methods: Between November 2014 and June 2017, consecutive patients who had underwent both CT‐guided PNB and EB via bronchoscopy for diagnosis of pulmonary lesions were evaluated retrospectively. Tissue samples were submitted for pathological examination, acid‐fast bacilli, TB RT‐PCR, and mycobacterial culture. Sensitivities of the two methods alone or in combination were calculated and compared using Fisher's exact test. Results: Sixty‐seven patients (46 men and 21 women) were enrolled and could be diagnosed (32 malignant, 18 TB, and 17 benign). A final diagnosis of either malignant or TB diseases was made in 34 (68.0%) patients for CT‐guided PNBs, 19 (38.0%) patients for EBs, and 42 (84.0%) patients for the combination of both methods. Further statistical analysis showed significant difference in sensitivity between CT‐guided PNBs, or the combination of both methods, and EBs (all P < 0.05), and no difference between CT‐guided PNBs and the combination ( P > 0.05). However, the combination of both methods appears to have the highest sensitivity in the detection of malignancies or TB diseases. Conclusion: Compared with EB, CT‐guided PNB has a high diagnostic yield for the detection of TB and malignancy in patients with multifocal pulmonary lesions with endobronchial involvement. When the two biopsies are combined, it appears to provide an incremental diagnostic value for the pulmonary lesions.